PENGEMBANGAN MODEL PERMAINAN BOLA BASKET RING DATAR PADA SISWA KELAS VII SMPN SATU ATAP TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to produce a model of learning the game of basketball a basketball game flat ringfor class VII SMP One Roof Lerep Unggaran Western District of Semarang District in teaching physicaleducation . The analysis procedure includes product development product that will be created , developed theinitial product , expert validation and revision , testing and revision of small groups , large groups and test thefinal product . The data was collected using a questionnaire derived from expert evaluation , as well as usingfield observations obtained from the students . The data analysis technique used is descriptive percentages .From the test results obtained by the expert average percentage results of the analysis of the product by 94.2 %with the criteria of